2001
DOI: 10.1104/pp.126.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Binding Activity of Pea Lectin Enhances Heterologous Infection of Transgenic Alfalfa Plants by Rhizobium leguminosarum biovar viciae  

Abstract: Transgenic alfalfa (Medicago sativa L. cv Regen) roots carrying genes encoding soybean lectin or pea (Pisum sativum) seed lectin (PSL) were inoculated with Bradyrhizobium japonicum or Rhizobium leguminosarum bv viciae, respectively, and their responses were compared with those of comparably inoculated control plants. We found that nodule-like structures formed on alfalfa roots only when the rhizobial strains produced Nod factor from the alfalfa-nodulating strain, Sinorhizobium meliloti. Uninfected nodule-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 47 publications
2
40
0
2
Order By: Relevance
“…Since 1989, several studies using transgenic plants have lent support to this hypothesis because transgenic roots expressing heterologous lectins are capable of being nodulated by the heterologous rhizobial species (Diaz et al, 1989;Kijne et al, 1997;Hirsch, 1999). For this effect, the sugar-binding site of the lectin is required (Diaz et al, 2000;van Rhijn et al, 2001), and the latest results suggest that exopolysaccharide rather than Nod factors may be the critical rhizobial component for extension of the host range (van Rhijn et al, 2001). The lectins have been suggested to function as a glue, sticking the two partners together for Nod factors to operate, or as a cloaking device to avoid recognition as a pathogen, or as an element in signaling and friend recognition (Hirsch, 1999).…”
mentioning
confidence: 96%
“…Since 1989, several studies using transgenic plants have lent support to this hypothesis because transgenic roots expressing heterologous lectins are capable of being nodulated by the heterologous rhizobial species (Diaz et al, 1989;Kijne et al, 1997;Hirsch, 1999). For this effect, the sugar-binding site of the lectin is required (Diaz et al, 2000;van Rhijn et al, 2001), and the latest results suggest that exopolysaccharide rather than Nod factors may be the critical rhizobial component for extension of the host range (van Rhijn et al, 2001). The lectins have been suggested to function as a glue, sticking the two partners together for Nod factors to operate, or as a cloaking device to avoid recognition as a pathogen, or as an element in signaling and friend recognition (Hirsch, 1999).…”
mentioning
confidence: 96%
“…Control plants and transgenic plants that expressed mutant pea lectin did not form nodules or infection threads when inoculated with low numbers of the same strain (171). Results such as these suggest that cell-cell contact and specific binding of compatible bacteria to root tips are important for infection and infection thread formation, because they result in the exposure of infectible root hair tips to the proper symbiont and hence to a high localized concentration of the Nod factors needed to trigger root hair curling and infection thread formation (79,171). A direct test of the importance of host lectins in promoting infection and invasion would be very interesting.…”
Section: Adhesion Of Rhizobia To Root Hairsmentioning
confidence: 99%
“…These lectins localize to root hair tips and are thought to help convey host-symbiont specificity by binding simultaneously to the plant cell wall and to saccharide moieties on the surfaces of compatible bacteria (41,43,79). A series of experiments in which a variety of transgenic plants expressed lectins from other species of legumes has shown that the presence of heterologous lectins often allows transgenic plants to respond to symbionts that are usually noncompatible, provided that the heterologous lectin can bind to the noncompatible bacteria and provided that the noncompatible bacteria make the proper Nod factor (42,79,171,172). For example, transgenic alfalfa that expressed pea lectin formed nodules and infection threads when inoculated with low numbers of R. leguminosarum bv.…”
Section: Adhesion Of Rhizobia To Root Hairsmentioning
confidence: 99%
“…A Zeiss Axiophot light microscope in conjunction with epifluorescence was used for observation of attached fluorescent rhizobia. Roots inoculated with Rm1021/gusA were stained as previously described 35 and examined under bright field optics.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, three-day-old wild-type M. alba seedlings of U389 and the Masym mutants were transferred to sterilized square dishes (Fisher Scientific International Inc., Hampton, NH) containing 1% Phytagar-solidified, one-quarter strength Hoagland's medium minus nitrogen (N), 34 and subsequently spot-or flood-inoculated with the wild-type controls, Sinorhizobium meliloti Rm1021 or Rm1021 carrying gusA, constructed as described earlier. 35 For studies of root hair deformation, only the wild-type M. alba and the Masym3 mutant, BT70, were examined. The roots were inoculated with either Rm1021 or the mutant strains, a Nod -S. meliloti (SL44: Cytokinin Triggers ENOD40 Expression in Melilotus DnodD1ABC) or a Nod -/pTZS + strain, which is SL44 carrying the trans-zeatin synthase gene of Agrobacterium tumefaciens.…”
Section: Methodsmentioning
confidence: 99%